The Use of Poster Masks in the Application of Project Based Learning Models in Illustration Drawing Materials - Dibba Gazwami; Budiwirman Budiwirman; Darmansyah Darmansyah (International Journal of Educational Dynamics, 2022)
In the Era of the Industrial Revolution 4.0, which is sweeping all life, the world of education must be able to adapt to technological knowledge, which is a competency that must be mastered to support the improvement of the learning process. Meanwhile, for students themselves, mastery of technology can support thought processes and mastery of science and technology. The industrial revolution in the 21st-century has a major influence on the mindset and also the needs that students must have as Soft Skills so that it is referred to as 21st-century learning. various age levels, educational levels, and fields of study, you can adjust to the conditions of the school. One of the learning models referred to is Project Based Learning. Meanwhile, material for drawing illustrations that are by the demands of 21st-century learning and used in Project Based Learning learning is using a poster maker or making posters with application-based digital techniques.